Fertility Status of Soil in the Tea Garden Belts of Golaghat District, Assam, India - Bhupen K. Baruah; Bhanita Das; Chitrani Medhi; Abani K. Misra (Journal of Chemistry)
The increasing land use intensity without adequate and balanced use of chemical fertilizers and with little or no use of organic manure have caused severe fertility deterioration of our soils resulting in stagnating or even declining of crop productivity in Assam. The need of the hour is to achieve substantially higher crop yield than the present yield levels from our limited land resources on a sustainable basis. A study was carried out in the paddy fields of tea garden belts namely, Rungagora, Balijan, Banwaripur, Khomtai, Rungajaun, Lattakoojan, Borjan, Behora, Negheriting, and Borsapori of Golaghat district of Assam to investigate the fertility status of soil during 2008–2010. Results of the present study showed that soil solutions were acidic in nature in all seasons. Medium-to-high BD, medium SOM, medium-to-high available N and available phosphorous, and low availability of potash showed that soils were not sufficiently fertile for crop production. Depending on the SOM, available N, available P, and exchangeable K in soil, the study areas were grouped in to six fertility classes as MMML, MMHL, MMMM, MHHL, MHHM, and MMHM. Student t-test values of all the parameters with control sample showed statistically significant results for SOM, available N, and available P in both seasons (dry and wet) and EC in wet seasons and bulk density in dry season only.